Changes in gut microbial metagenomic pathways associated with clinical outcomes after the elimination of malabsorbed sugars in an IBS cohort. (3rd May 2020) - Mack, A.; Bobardt, J.S.; Haß, A.; Nichols, K.B.; Schmid, R.M.; Stein-Thoeringer, C.K.
ABSTRACT: Specific diets to manage sugar malabsorption are reported to reduce clinical symptoms of irritable bowel syndrome (IBS). However, the effects of diets for malabsorbed sugars on gut microbiota signatures have not been studied, and associations with clinical outcomes in IBS have not been characterized. 22 IBS patients positively tested for either lactose-, fructose-, sorbitol- or combined malabsorptions were subjected to 2-weeks sugar elimination and subsequent 4-weeks re-introduction. 7 IBS patients tested negative for sugar malabsorption were used as controls. Nutrition and clinical symptoms were recorded throughout the study. Fecal samples were serially collected for 16S rRNA amplicon and shotgun-metagenome sequencing. Dietary intervention supervised by nutrition counseling reduced IBS symptoms during the elimination and tolerance phases. Varying clinical response rates were observed between subjects, and used to dichotomize our cohort into visual analogue scale (VAS) responders and non-responders. Alpha -and beta-diversity analyzes revealed only minor differences regarding 16S rRNA-based fecal microbiota compositions between responder and non-responder patients during baseline or tolerance phase. In shotgun-metagenome analyzes, however, we analyzed microbial metabolic pathways and found significant differences in pathways encoding starch degradation and complex amino acid biosynthesis at baseline between IBS controls and malabsorbers, and notably, between diet responder and non-responders. Faecalibacterium prausnitzii, Ruminococcus spp . and Bifidobacterium longum largely informed these metabolic pathways. Our study demonstrates that diet interventions for specific, malabsorbed carbohydrates reshaped the metagenomic composition of the gut microbiota, with a small community of bacterial taxa contributing to these changes rather than a single species.